APOE influences working memory in non‐demented elderly through an interaction with SPON1 rs2618516. Issue 7 (24th March 2018) - Liu, Zhen; Dai, Xiangwei; Tao, Wuhai; Liu, Huilan; Li, He; Yang, Caishui; Zhang, Junying; Li, Xin; Chen, Yaojing; Ma, Chao; Pei, Jing; Mao, Haohao; et al.
Abstract: Exploring how risk genes cumulatively impair brain function in preclinical phase (i.e., in cognitively normal elderly) could provide critical insights into the pathophysiology of Alzheimer's disease (AD). Working memory impairment has always been a considerable cognitive deficit in AD, which is likely under complex genetic control. Though, the APOE ɛ4 allele could damage the working memory performance in normal elderly, dissociable results have been reported. This allele may exert specific effects in contexts with other genetic variants. The rs2618516 in the spondin 1 gene ( SPON1 ) has been associated with AD risk and brain structure in the elderly. SPON1 may interact with APOE through processing the amyloid precursor protein and suppressing amyloid‐β levels. Using neuropsychological tasks from 710 individuals, we found significant SPON1 × APOE genotype interactions in working memory and executive function performances. Moreover, such interaction was also found in regional brain activations based on functional magnetic resonance imaging data with the n‐back working memory task performed in a sub‐cohort of 64 subjects. The effects of ɛ4 allele on activation of right inferior frontal gyrus, triangular part (IFGtriang.R) were modulated by rs2618516 in a working memory task. Furthermore, lower IFGtriang.R activation was associated with better cognitive functions. Moreover, the IFGtriang.R activation could mediate the impacts of SPON1 × APOE interactions on working memory performance. These findings suggested the importance of weighing APOE effects on brain activation under the working memory task within the context of the SPON1 genotype.